Pengaruh Aktivitas Mewarnai Damar Kurung Terhadap Perkembangan Motorik Halus Anak Usia Dini - Ubaidillah; Purnawati, Putri; Nisa’ Karimah, Alviyatun; Muchibbah, Musyi’fatul; Indah Ali, Sayumi; Sofiul Inayah, Nisrina (UIR PRESS, 2024)
Directed coloring activities can be said to be activities that provide students with the opportunity to color based on imagination and in accordance with the teacher's instructions. The aim of this research is not only to determine the increase in children's creativity, but also to determine the effect of using resin brackets as a medium to improve children's fine motor skills at the Al-Walida Bungah Gresik Kindergarten. The method used in this research is quantitative using primary and secondary data sources. The population and sample used was 25 children. Data collection techniques used observation, interviews and documentation methods. Meanwhile, technical data analysis uses validity and reliability tests, and simple linear regression analysis. The results of the regression equation analysis, the regression coefficient This may be because the activity of coloring resin brackets can indirectly train children's motor skills. The results of the research are based on data analysis and hypothesis testing, so the conclusions that can be put forward in this research are as follows: the resin bracket coloring activity has a significant influence on the fine motor development of Group A children (4-5 years old). This is shown by the t-count value of 2,598> 1,717 with a significance value of 0.02> 0.05 with a significance level of 5%. It is hoped that research like this can provide input for educators to be more creative in providing coloring activities with interesting media, so that Children are interested every time they see the picture shown by the teacher.